Efektivitas Model Partner In Learning dalam Meningkatkan Kemampuan Kolaborasi pada Kegiatan Praktik Smkn 9 Bandung - Anindya Salsabila Putri Yusdiana; Laqueisha Ozora Putri Lubis; Victoria Pitauli Rajagukguk (Asosiasi Riset Ilmu Pendidikan Indonesia, 2026)
This study examines the effectiveness of the Partner in Learning model in enhancing students' collaboration skills during productive practice activities at SMKN 9 Bandung. Modern industrial demands require vocational school graduates to possess not only technical skills but also strong collaborative competencies. However, conventional teacher-centered learning approaches often limit students' opportunities for active social interaction. This research employed a qualitative descriptive approach with a case study design. Data were collected through semi-structured interviews with ten students from six different vocational programs at SMKN 9 Bandung, as well as non-participatory observation conducted during practice sessions in April 2026. Data analysis followed the interactive model of Miles, Huberman, and Saldana (2014), comprising data reduction, data display, and conclusion drawing. Source triangulation was applied to ensure data credibility. The findings reveal that the Partner in Learning model is effective in improving students' collaborative abilities, particularly in terms of active communication, teamwork, and shared responsibility in completing practice tasks. Nevertheless, challenges remain, including a classroom environment that is not yet fully conducive to open discussion and students' low initiative in independently seeking additional references. These findings imply that the success of this model depends on a supportive learning environment and strategies to foster student learning autonomy.